أقسام المکتبات والمعلومات المعتمدة من الهیئة القومیة لضمان الجودة والاعتماد فى مصر : دراسة تحلیلة مقارنة - د. هبة مدحت المنباوى (المجلة الدولية لعلوم المكتبات والمعلومات)
The research covers an important and vital topic in the field of qualityassurance and accreditation of the accredited programs in the libraries,documents and information departments in the faculties of Art at the publicuniversities, both for the bachelor's degree and through the standards issued bythe National Authority for Quality Assurance and Accreditation.The study presents the concept of total quality management andaccreditation in academic education, the definition of the National Authority forQuality Assurance and Accreditation, and the standards of the College of Artsand then the standard used in the social and human sciences.The study aimed to determine the number of libraries and informationdepartments in the faculties of Art at Egyptian Government Universities and todetermine the number of accredited bachelor's programs in the libraries andinformation departments in the faculties of Art in public universities in Egypt bythe National Authority for Quality Assurance, Accreditation and Access to pointsof difference and points of agreement between these programs.The study used the field approach to address the subject of the study andthe questionnaire as a tool to collect data on the programs of the sections.Then the study was followed by statistics to compare the programs of thefour departments in order to answer the study questions which are the answers totheir objectives.The departments are Libraries and Information Sciences Faculty of Arts,Ain Shams University, Department of Libraries and Information College of Arts,Sohag University, Library, Documentation and Information TechnologyDepartment, Faculty of Arts, Cairo University.